Impact of fertigation frequency on growth and yield parameters of baby corn (Zea mays) under drip irrigation - KUMAR, MUKESH; RAJPUT, T B S; PATEL, NEELAM (The Indian Journal of Agricultural Sciences, 2015)
The experiments were conducted at the research farm of Water Technology Centre, Indian Agricultural Research Institute, New Delhi during 2010–2011 for three consecutive seasons (October 2010- February 2011, April- July 2011 and August- November 2011) to study the impact of different fertigation frequencies and dripper discharge at different system operating pressures on growth parameters, corn yield and fodder yield of baby corn (Zea mays L.) crop. The study was planned with nine treatments which included dripper discharges at three system operating pressures(0.5 kg/cm2, 1.0 kg/cm2 and 1.5 kg/cm2) and three fertigation frequencies (biweekly, weekly and fortnightly). Growth parameters, viz. number of leaves per plant, plant girth, plant height, leaf area and Leaf Area Index (LAI) of baby corn during different growth stages were measured and recorded. There was a significant (P<0.05) effect of drip fertigation on number of leaves/plant, plant height, leaf area and leaf area index. Maximum number of leaves/plant (15.67), plant girth (57.29 mm), plant height (176.29 cm) and LAI (5.94) were observed under treatment T4 (biweekly fertigation with 1.41 l/h dripper discharge at 1.0 kg/cm2 system operating pressure) at 80 days after sowing (DAS) during second season whereas lower values of number of leaves/plant (11.33), plant height (150.40 cm), plant girth (41.07 mm) and LAI (4.90) were observed at 120 DAS under treatment T4 (fortnightly fertigation frequency with 1.71 l/h dripper discharge at system operating pressure of 1.5 kg/cm2) during third season fortnightly fertigation frequency at system operating pressure of 1.5 kg/cm2 during third season. Yield components of baby corn were not significantly affected by fertigation at different system operating pressures. However, different yield attributes of baby corn were significantly (P<0.05) affected by fertigation frequencies. Biweekly fertigation frequency at par with weekly fertigation schedule while a trend of significantly lower yields were recorded under fortnightly fertigation frequency. Highest yield of baby corn and fodder was recorded in biweekly fertigation schedule with 1.41 l/h dripper discharge at system operating pressure of 1.0 kg/cm2 (22.5 and 633.3 q/ha) followed by weekly fertigation schedule at system operating pressure of 1.0 kg/cm2 (22.0, 619.4 q/ha), respectively during second season. The lowest yields of baby corn and fodder (11.2 q/ha and 454.6 q/ha) were recorded in fortnightly fertigation frequency with 1.71 l/h dripper discharge at system operating pressure of 1.5 kg/cm2 during third season.